Sustainable practice for the management of guava mealybug, Ferrisia virgata with the combined effect of insecticides and entomopathogenic fungi - UNIYAL, ANKIT; SRIVASTAVA, POONAM (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2022 and 2023 at G B Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to evaluate the insecticides, entomopathogenic fungi (fungal bioagent) and their tank mixed combinations against mealybug, Ferrisia virgata (Cockerell) at fruiting stage of guava, Psidium guajava L. A total of 12 treatments including untreated control were taken and were categorized as chemical (insecticides), biological (entomopathogenic fungi) and chemical + biological (tank mixed combinations). It was found that treatment, spinetoram + Metarhizium anisopliae was most effective against the pest in both seasons, followed by spinetoram, spinosad + Metarhizium anisopliae and spinosad. The experiment was laid out on a randomized block design (RBD) with three replications. However, M. anisopliae was observed as the least effective treatment. Considering the groups, cumulative efficacy of two seasons showed that chemical + entomopathogenic fungi was the best with 54.79% control efficacy followed by chemical (CE = 51.10%) and biological (CE = 25.00%).